Attitudes about sexual disclosure and perceptions of stigma and shame - Cunningham, S (BMJ Group, 2002)
Methods: A household sample of 142 sexually active African-American youths, 13–19 years old, was questioned about STD related stigma (alpha = 0.89), STD related shame (alpha = 0.90), and perceptions about disclosure of sexual behaviours to a doctor or nurse (alpha = 0.81). Results: Among females, stigma was associated with increased anticipation of negative reactions to disclosure of sexual behaviours to a doctor or nurse (odds ratio (OR) = 0.319; 95% confidence interval (CI) =0.12 to 0.85) while shame was not. Stigma was also independently associated with STD related care seeking in the past year (OR = 0.296; 95% CI = 0.09 to 0.94) while shame was not. There was no association between stigma and shame with perceptions about disclosure or past care seeking in males. Perceived outcomes of disclosing sexual behaviours did not moderate the association of stigma, shame, and past STD related care seeking. Conclusions: Stigma about STDs may influence how female adolescents perceive reactions to disclosure of their sexual behaviour to healthcare providers. It may also be an important factor in their decision seek to STD related care. Perceptions about disclosure of sexual behaviour to a doctor or nurse do not change the relation of stigma or shame to past STD related care seeking.